SOCIAL CONSEQUENCES OF ENVIRONMENTAL RISKS IN MODERN SOCIETY (British Journal of Global Ecology and Sustainable Development, 2024)
The article analyzes environmental risks and their social consequences in the context of the problems of a modern industrial city. Their specific features are analyzed, the typology and methodology of sociological research of the social consequences of environmental risks are substantiated. It is emphasized that environmental risks have a dual nature: on the one hand, they carry an objective component of danger, the probability of an undesirable outcome in the final field of variability of events, on the other hand, subjective assessments and perception of this probability, formed in the context of the existing spatial, infrastructural and socio-ecological conditions.